Effectiveness Magnesium ammonium phospate (MAP) precipitation and filtration method in treatment of palm oil mill effluent (POME) - Nurul'ain , Othman (2013)
The process of oil extraction from palm oil industry resulted in the generation of liquid waste commonly known as palm oil mill effluent (POME). P0MB is a viscous brown liquid containinghigh concentrations of fine suspended solids, oil and grease andother contaminants. Several treatment technologies have been used for P0MB treatment, since the direct discharge of POME adversely affects the environment. Majority of palm oil mill uses conventional biological treatment of aerobic, anaerobic or facultative ponds which needs large area and long treatment periods. The conventional treatment system is quite inefficient andleads to environmental issues. The use of chemical precipitation method such as magnesium ammonium phosphate (MAP) precipitation has been studied and was found to be effective in treating landfill leachate. The key feature of this recovery technique is the combined removal of ammonium (NH4 + 3- ), phosphate (PO 4 ) and magnesium (Mg 2+) from supersaturated solutions. The by-product of this method is magnesium ammonium phosphate hexahydrate (MgNH 4 PO 4 6H2 O), which is commonly known as struvite. Extracting nutrient using MAP precipitation method may be beneficial in treatment of POME. However, MAP precipitation alone would not be sufficient to remove contaminants concentration regulatory discharged limits. In this study, MAP precipitation method was used to treat raw POME obtained from Sime Darby, Jabor palm oil mill. Additionally, filtration using activated carbon (AC) and glass carbon (GC) was also used further treatthe P0MB. Results indicated that, after treatment process, the lowest, turbidity 21,433 NTU, COD is 66,300 mgIL, TOC is 26,600 mg/L and oil and grease is 8,269 mg/L of treated POME were achieved. Although both methods reduced the contaminant concentration to desired limits, the final COD and TOC concentration is much greater than allowable standard limits. It was also observed that for all water quality parameters considered, GC filter performed slightly better than of AC filter.